Total Blindness Following Anaphylactic Shock due to Co-Amoxiclav Treatment - Shushtarian, Seyed Mohammad Masoud; Vahid Dastjerdi , Mehdi (Journal of Ophthalmic and Optometric Sciences, 2020)
Anaphylactic shock is a rare but severe allergic reaction most often caused by an allergy to food, insect bites, or certain medications. Co-amoxiclav is an antibiotic medication used to treat many bacterial infections. In the present work, the authors report an 82-year-old female patient suffering from total blindness after anaphylactic shock after taking the first dose of co-amoxiclav.